PENERAPAN METODE PEMBELAJARAN MIND MAPPING (PETA PIKIRAN) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SD NEGERI 29 PEKANBARU - Rotila Nopidah Ayu; Zariul Antosa; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research was done because of the low of learning outcomes on social science subject (IPS) of fifth grade students of SD Negeri 29 Pekanbaru. It can be seen from the minimum completeness Criteria (KKM) from that school is 75. From 36 students who reach the KKM was 17 (47.22%) and who did not reach the KKM was 19 (52.78%) with class average was 67.77. The purpose of this research is to improve the learning outcomes on social science of fifth grade students of SD Negeri 29 Pekanbaru with the application of learning method of mind mapping. This study presents the results of learning value obtained from daily test before the action with average was 67.77 became 74.16 on cycle I, and increasing again became 81.38 in cycle II. The activity of the teacher in the cycle I of the first meeting by a score of 23 (71.87%) with enough category. And in the second meeting score was 25 (78.12%) with good category. In Cycle II of first meeting score was 28 (87.5%) with verygood category. In the second meeting of the score was 30 (93.75%) with verygood category. The activity of the students at the first meeting on cycle I get score 21 (65.62%) with enough category, in the second meeting score was 25 (78.12%) with good category. In first meeting of cycle II get score 28 (87.5%) with verygood category, and in the second meeting get score 29 (90.62%) with verygood category. Based on the results of this research, it can be concluded that the application of learning method of mind mapping can improve learning outcomes on social science of fifth grade students of SD Negeri 29 Pekanbaru.Keywords: Mind Mapping, Leraning Outcomes, Social Science